2003
DOI: 10.1161/01.atv.0000094235.78783.d1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin II in Altered Expression of Molecules Responsible for Coronary Matrix Remodeling in Insulin-Resistant Diabetic Rats

Abstract: Objective-Coronary remodeling based on collagen abnormalities in diabetes might be associated with potential interactions between the matrix metalloproteinase (MMP) system, which regulates extracellular matrix turnover, and the fibrinolytic system, which is involved in the fibrin degradation process. We characterized the profiles of the MMP and fibrinolytic systems in insulin-resistant diabetic rat hearts. Methods and Results-By immunohistochemistry and in situ hybridization, transforming growth factor-␤ 1 (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 39 publications
6
43
0
9
Order By: Relevance
“…20 Ang-II also stimulates cardiac collagen production by promoting TGF-b1 synthesis through AT 1 R receptor activation. 21 In addition, AT 1 R activation has a role in the molecular changes associated with coronary matrix remodeling in diabetes. 21 Furthermore, AT 1 R blockade reduces myocardial hypertrophy, decreases myocardial fibrosis and attenuates cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Ang-II also stimulates cardiac collagen production by promoting TGF-b1 synthesis through AT 1 R receptor activation. 21 In addition, AT 1 R activation has a role in the molecular changes associated with coronary matrix remodeling in diabetes. 21 Furthermore, AT 1 R blockade reduces myocardial hypertrophy, decreases myocardial fibrosis and attenuates cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, AT 1 R activation has a role in the molecular changes associated with coronary matrix remodeling in diabetes. 21 Furthermore, AT 1 R blockade reduces myocardial hypertrophy, decreases myocardial fibrosis and attenuates cardiac remodeling. 22 Consistent with previous studies, 21,22 we have also observed increased expressions of TGF-b1 and collagen-III mRNA in group V, and these increased mRNA levels were suppressed by telmisartan treatment (Figures 3a-c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Insulin resistance and chronic hyperinsulinemia increase the local activity of renin-angiotensin-aldosterone system and expression of angiotensin II receptors in vascular tissue, thus leading to arterial wall hypertrophy and fibrosis. 39,40 Impaired glucose tolerance also enhances nonenzymatic glycation and crosslinking of collagen, leading to stiffening of arteries. 41 These mechanisms may in part underlie the here observed associations between the cardiometabolic risk markers and arterial distensibility.…”
Section: Discussionmentioning
confidence: 99%
“…MSC have been shown to differentiate into several cell types, including cardiomyocytes, endothelial cells, neurons, hepatocytes, epithelial cells and adipocytes, characteristics coupled with capacity of self renewal. Chronic hyperglycemia is responsible for myocardial remodelling leading to ventricular dysfunction with hypertrophy and apoptosis of cardiomyocytes, microcirculatory defects, altered extracellular matrix and matrix metalloproteinasis (Jesmin et al, 2003). MSC can induce myogenesis and angiogenesis by different mitogenic, angiogenic and antiapoptotic factors, such as VEGF, IGF-1 and HGF .…”
Section: Msc Treatment Of Complications Of Diabetes Mellitusmentioning
confidence: 99%